Haematology, genetics and molecular epidemiology of deletional alpha thalassaemia in Malaysia - Mohd Yacob, Aliza (2011)
Alpha thalassaemia is the most common autosomal recessive single gene disorder in Southeast Asia, encountered in increasing numbers all over the world and heterogenous. Deletions of all four alpha thalassaemia genes (--/--) result in fetuses mostly die before or shortly after birth known as Hb Barts hydrops foetalis syndrome. It also caused serious maternal complications in pregnancies in which without medical care half were estimated to die. Deletions of 3 alpha thalassaemia genes (--/-) is known as HbH disease with moderate anaemia, usually was similarly seen in the Malays and Chinese. In contrast, antenatal diagnosis for alpha thalassaemia reported Hb Barts hydrops foetalis (--/--) mostly in the Chinese. Thalassaemia studies among blood donors of 91.3% Malays found out that 30% were anaemic with all donors had a negative H-inclusion test, which is usually positive with double deletions (--/). Malaysia is a multiethnic country with mix marriages and 4.5% of Chinese-Malaysian is carriers of 0 thalassaemia (--/). Therefore the purpose of this study was to determine the current deletional alpha thalassaemia status and deletional alpha thalassaemia burden in our population. Changes in deletional alpha thalassaemia gene frequency may change the deletional alpha thalassaemia burden. In this study haematology, genetics and molecular epidemiology of deletional alpha thalassaemia were looked at and carrier detection of common deletions was carried out. This will identify phenotypic characteristics, type of deletions and genotypes present, determine prevalence, estimate disease burden of deletional alpha thalassaemia and determine foetal genotype from pregnancies at risk of deletional Hb Barts hydrops foetalis in the country. Standard haematology protocol, DNA studies and statistical analysis of qualitative and quantitative were applied. A cross sectional study was carried out on 405 samples. These were 238 EDTA blood from blood donors from Universiti Putra Malaysia, 15 DNA of 5 Hb Barts hydrops foetalis (--/--) and 10 alpha thalassaemia spouses (--/) from Universiti Malaya Medical Centre, 72 EDTA blood from HbH disease (--/-) families from Institute for Medical Research and 80 DNA from blood donors from National Blood Bank. Blood count/blood film, HPLC, haemoglobin electrophoresis and multiplex PCR for detecting the 5 most common gene deletions were carried out. These are the common --SEA in Southeast Asia, the ethnic origins --THAI and --FIL, the world common single deletions -3.7 and -4.2. Multiplex PCR using validated primers was developed using samples from families of HbH disease, detected the --SEA, --THAI, --FIL and -3.7 giving 5 genotypes. This was compared with conventional method using samples from National Blood Bank and gave 100% accuracy, sensitivity and specificity for --SEA. --FIL, --THAI and -3.7 were also detected. In blood donors from Universiti Putra Malaysia, MCV < 80 fL was identified in 16.5% (with exclusion of Indians), deletional thalassaemia prevalence was 7.4% (3.5% double and 3.9% single deletions), equally distributed among Malays and Chinese. The most common double deletion detected was --SEA and -3.7 for single followed by -4.2. The prevalence was 5.3% in the Malays with the most common was -3.7 (4.3%), 8.5% in the Chinese with 5.4% --SEA indicating an increase from 4.5% 0 thalassaemia (--/) and 0.4% in others. All the --SEA were with MCV<68 fL and MCH <22 pg. The projected number of pregnancies each year at risk of deletional Hb Barts hydrops foetalis syndrome and HbH disease are 30 and 120 in Malays, 250 and 150 in Chinese, 640 of both and on average 600 and 669 respectively. A typical thalassaemia phenotype was observed in HbH disease, and carriers of 0 and + thalassaemia. Real-time quantitative PCR (TaqMan®) with validated primers was optimized for --SEA. Fetal genotype values ofSEA-BRN were 0.6 to 1.6 for (--SEA/--SEA), 0.2 to 0.5 for (--SEA/) and 0 for (/) giving distinctly different values. The methods used were simple, reliable and useful in monitoring allele status. Identified carriers can be counseled and DNA from pregnancies at risk for (--/--) can be analysed. These will help in increasing awareness among carriers, bringing down deletional thalassaemia births and eventually lower the disease burden in Malaysia.